Acute effects of isometric conditioning activity with different distribution contraction on countermovement jump performance in resistance trained participants - Jakub Jarosz; Milosz Drozd; Dawid Gawel; Michal Wilk; Jonatan Helbin; Michal Krzysztofik (Scientific Reports)
Abstract The aim of this study was to compare the effects of 3 sets of isometric conditioning activity (ICA), each with an equal total duration (9 s per set) but with different distributions contractions, on force production during ICA and subsequent countermovement jump (CMJ) performance. Fifteen resistance-trained males participated in this study (age: 22.1 ± 2.4 years; body mass: 85.1 ± 9.7 kg; height: 181.3 ± 6.5 cm; relative one-repetition maximum (1RM) in back squat: 1.59 ± 0.32 kg/kg of body mass). Participants completed 3 conditions, each consisting of ICA in the half-back squat with a pushing isometric muscle action (PIMA) position at a 120-degree knee angle against an immovable barbell, differing in repetition distribution: 3 sets of 9 repetitions lasting 1 s each (SUST-1), 3 sets of 3 repetitions lasting 3 s each (SUST-3), 3 sets of single repetitions lasting 9 s (SUST-9), and a control condition (CTRL) without ICA. A 1-minute rest was allowed between sets. Approximately 3 min pre-ICA and at 15 s, 3-, 6-, 9-, and 12-minutes post-ICA, the CMJ performance was assessed. Moreover, peak force (PF) production, and force generated at 100 (Force100) and 200 ms (Force200) during each ICA were evaluated. A two-way repeated measures ANOVA indicated a main effect of time on CMJ height (F = 2.674; p = 0.029; ηp²=0.171) but did not show significant differences between conditions (F = 0.934; p = 0.434; ηp²=0.067) or interactions (F = 0.826; p = 0.648; ηp²=0.060). Post-hoc comparisons indicated a significant decrease in CMJ height at the 9th minute compared to the 3rd minute (35.7 ± 5.6 cm vs. 36.8 ± 5.5 cm post-CA; d = 0.161; p = 0.048). In addition, no significant interactions or main effects were found for CMJ contraction time, PF and Force100 during ICA. However, a main effect of condition was demonstrated on Force200 (F = 19.181; p < 0.001; ηp²= 0.013). Post-hoc comparisons revealed higher Force200 values in SUST-1 (mean difference [MD] = 549 ± 137 N; d = 1.049; p < 0.001) and SUST-3 (MD = 348 ± 112 N; d = 0.665; p = 0.002) compared to the SUST-9 condition. None of the ICAs used in the present study had any effect on the CMJ performance. However, the significantly higher Force200 values noted in the SUST-1, and SUST-3 conditions compared to the SUST-9 condition suggest that the specific distributions of isometric contraction influence the force generated during their execution.